Modul Elektronika Berbasis Mikrokontroler sebagai Sistem Pengaman pada Mobil Terintegrasi dengan Engine Immobilizer - Arief Goeritno; Muhammad Yusuf Afandi (Jurnal Rekayasa Elektrika, 2019)
An electronic module based on the ATmega32 microcontroller as a security system for cars that integrated into the engine immobilizer has been created. Three main things in this study, namely programming and verification tests, making an initial security system with a minimalist structure, and validation tests. Programming for the microcontroller system through algorithm determination and syntax writing, while the verification test is done through uploading the program syntax to the Proteus application and implementing the simulation. Determining the algorithms and writing the syntax through a number of steps, namely pin configuration, variable declarations, constant declarations, initialization, main programs, retrieve and send data, and output. The simulation assisted by the Proteus application is in the form of giving two kinds of commands/inputs to the sensor, namely one input data in the form of human existence or human motion to the passive infrared receiver sensor and one input of human fingerprint initialization data to the fingerprint sensor. The simulation results according to the order of the fingerprint sensor and passive infrared receiver in the form of a display on the Virtual Terminal. The minimalist structure of the system is composed of circuit diagrams, physical forms, and integrated wiring on the ATmega32 microcontroller system. The performance of the security system is shown, that the results of monitoring when the sensor is given input "human existence (motion)", the fingerprint sensor blinks (on) and when the fingerprint sensor blinks which means ready to receive input data in the form of "Human Initialization (fingerprint)" for activating actuators and starter system on the car. Giving input commands to the sensor passive infrared receiver and fingerprint has functioned for the appointment of performance, that the initial security system has been integrated with the main security systemand attached to the car.